2015
DOI: 10.1007/s11682-015-9434-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hallucinations and FDG-PET in dementia with Lewy bodies

Abstract: Visual hallucinations are common in dementia with Lewy bodies (DLB), although their etiology is unclear. This study aimed to investigate the relationship between severity and frequency of hallucinations and regional brain glucose metabolism. We performed brain FDG-PET scanning on 28 subjects with DLB (mean age 76). The neuropsychiatric index (NPI) was used to assess frequency and severity of hallucinations. We used the SPM package to investigate voxelwise correlations between NPI hallucination score (severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…One could hypothesize that dysfunction in this network of structures may contribute to the overlapping features observed across PCA and DLB. Occipital hypometabolism has been associated with the presence of DLB clinical features (27)(28)(29), and visual hallucinations, parkinsonism, and RBD were observed in some of our PCA patients, as has previously been reported (13). Atrophy of the primary visual cortex and thalamus has indeed been associated with the presence of visual hallucinations in PCA (13), and parietal and thalamic atrophy has been associated with parkinsonism in PCA (30).…”
Section: Discussionsupporting
confidence: 71%
“…One could hypothesize that dysfunction in this network of structures may contribute to the overlapping features observed across PCA and DLB. Occipital hypometabolism has been associated with the presence of DLB clinical features (27)(28)(29), and visual hallucinations, parkinsonism, and RBD were observed in some of our PCA patients, as has previously been reported (13). Atrophy of the primary visual cortex and thalamus has indeed been associated with the presence of visual hallucinations in PCA (13), and parietal and thalamic atrophy has been associated with parkinsonism in PCA (30).…”
Section: Discussionsupporting
confidence: 71%
“…Cell loss in the nucleus basalis of Meynert (Ch4 intermediate part) affects the cholinergic innervation to occipital–parietal cortical regions in DLB (Liu, Chang, Pearce, & Gentleman, ). At group level, occipital hypometabolism was also associated with DLB core clinical symptoms (e.g., (Albin et al, ; Caminiti, Alongi, et al, ; Chiba et al, ; Firbank, Lloyd, & O'Brien, ; Graff‐Radford et al, ; Iaccarino et al, ; Ishii et al, ; Kantarci et al, ; Klein et al, ; Minoshima et al, ; Perani et al, ; Perneczky et al, ; Perneczky et al, ; Satoh et al, ; Teune et al, )). A recent study, clustering DLB patients based on their individual brain hypometabolism maps, found that patients with more severe occipital involvement present a higher prevalence of VH, visuospatial, and visuoperceptive deficits (Caminiti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Occipital hypometabolism and reduced regional cerebral blood flow (rCBF) are characteristics of DLB 114,115 , and have been linked to visual hallucination severity 116 . Whether the same regions exhibit reduced metabolism and rCBF in PD psychosis is less clear.…”
Section: Imaging and Electrophysiologymentioning
confidence: 99%